2013
DOI: 10.1073/pnas.1309211110
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Golgi casein kinase

Abstract: The family with sequence similarity 20 (Fam20) kinases phosphorylate extracellular substrates and play important roles in biomineralization. Fam20C is the Golgi casein kinase that phosphorylates secretory pathway proteins within Ser-x-Glu/pSer motifs. Mutations in Fam20C cause Raine syndrome, an osteosclerotic bone dysplasia. Here we report the crystal structure of the Fam20C ortholog from Caenorhabditis elegans. The nucleotide-free and Mn/ ADP-bound structures unveil an atypical protein kinase-like fold and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 46 publications
1
89
1
Order By: Relevance
“…The Fam20B insert from the pCCF vector was also subcloned into the pQCXIP retroviral vector for generating stable cell lines. GalT-II and Fam20B ORFs were subcloned into a modified pSMBP baculovirus vector for protein production (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fam20B insert from the pCCF vector was also subcloned into the pQCXIP retroviral vector for generating stable cell lines. GalT-II and Fam20B ORFs were subcloned into a modified pSMBP baculovirus vector for protein production (19).…”
Section: Methodsmentioning
confidence: 99%
“…Fam20B belongs to a recently identified family of secretory pathway kinases that includes Fam20C, which phosphorylates secretory proteins within a highly conserved Ser-X-Glu/pSer motif (7,18). Although Fam20B shares nearly 60% sequence similarity with Fam20C, it does not phosphorylate proteins; rather, Fam20B has been reported to phosphorylate the xylose residue within the tetrasaccharide linkage of α-thrombomodulin (6,19). To test whether authentic PGs could serve as substrates for Fam20B, we took advantage of the fact that xylose phosphorylation on mature PGs has been reported to be substoichiometric (20).…”
Section: Significancementioning
confidence: 99%
“…The presence of these various VWA and chitin-binding domains suggests that these proteins might participate in structuring the chitin/protein nacre scaffold. In addition, we identified other ECM-related proteins, such as DMP-like, MSP130-like, mytilin3-like, ANF-receptor containing or Ca-binding proteins, for which homologues have previously been described from other proteins associated with biomineralization [30][31][32]. The involvement of these proteins in biomineralization processes is discussed below.…”
Section: Pif-like and Pif-related Proteinsmentioning
confidence: 98%
“…Notably, Rafaelsen et al (12) identified a novel missense mutation in Fam20C that substituted Thr 268 with a Met in two compound heterozygous brothers who had elevated serum intact FGF23 and hypophosphatemia. Threonine 268 (Thr 175 in Caenorhabditis elegans) is highly conserved within the Fam20C subfamily, and the C. elegans Fam20 crystal structure revealed that this Thr is located in the glycine-rich loop (β1-β2), a region important for nucleotide binding (35) (Fig. 5 A and B).…”
Section: Incomplete Inhibition Of Fgf23 O-glycosylation By Fam20c T268mmentioning
confidence: 99%